Pelatihan Pembuatan Beton bagi Siswa SMK N 3 Semarang - Muhammad Latif; Bambang Purnijanto; Hendra Masvika (Faculty of Engineering, Universitas Semarang, 2024)
Concrete is a solid mixture that hardens, consisting of components such as cement, sand, gravel, and water that are mixed. Civil engineering construction is related to concrete, including the construction of roads, buildings, dams, houses, and irrigation channels. Considering the importance of knowledge related to concrete, students of SMK N 3 Semarang who are majoring in construction engineering and housing need to be well informed. Many vocational high school students are still unaware of the proper process of making concrete that meets the desired quality standards. Students of SMKN 3 Semarang, who are expected to be able to work immediately after completing their studies, need to be equipped with knowledge about the concrete-making process. The purpose of this activity is to improve the knowledge of SMKN 3 Semarang students regarding the quality of concrete materials, the making of K-225 quality concrete, and the value of the concrete slump test. The PkM team from Universitas Semarang conducted training on making concrete for SMK N 3 Semarang students using discussion methods and laboratory practice. As a result of this training, the majority of students understand the process of making concrete in terms of material quality, K-225 concrete mix design, and slump test testing.